KONSUMERISME PENGGEMAR K-POP DI KOTA DENPASAR - Yuandhini, B. Warfanni Azzura; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT The aim of this research is to know how the consumerism behavior of K-Pop fans in Denpasar. This research is qualitative research that used Consumer Society Theory proposed by Jean P. Baudrillard to analyze the behavior of K-Pop fans. K-Pop music, which is supported by the singers, evidently made their fans became loyal. Loyal behavior of the K-Pop fans, can be proved by the consumption level of K-Pop fans toward K-Pop commodities that eventually caused consumerism behavior. The motivations of K-Pop fans to consume K-Pop commodity are as their appreciation toward their idol, a support to their idol, investment for the fans, a form of inner gratification for the fans, and a form that indicate their identity. The efforts of the K-Pop fans to consume K-Pop commodity are saving their money, working, and starting their own business. The consumption behavior of the K-Pop fans is often overwhelming for non-fan communities. However, for the K-Pop fans, the behavior they do and commodity they have are very meaningful and valuable to them. Keywords: Consumerism, Consumer Society, Fans, K-Pop